Effect of applying metal artifact reduction algorithm in cone beam computed tomography in detection of vertical root fractures of teeth with metallic post versus digital intraoral radiography - Islam Shawky Shaker; Nashwa Salah Mohamed; Ahmed Mohamed Abdelsamad (Wolters Kluwer Medknow Publications, 2019)
Background: Conventional radiographs are not an efficient diagnostic imaging modality to detect vertical root fracture. Cone-beam computed tomography (CBCT) is a three-dimensional imaging modality that overcomes the limitations of conventional radiography in the detection of vertical root fractures (VRFS), although metallic structures produce artifacts in the produced images and since most of the teeth with VRF are endodontically treated and have metallic posts in root canal so fracture detection may be difficult. Aim: This study aimed to determine the diagnostic accuracy of CBCT using metal artifact reduction algorithm in detection of VRF of teeth with metallic posts compared to digital intraoral radiography. Materials and Methods: One hundred and twenty single-rooted extracted human teeth were endodontically treated then placed in an acrylic block and metallic posts were inserted. The teeth roots were divided into two groups; one with induced VRF and the other having intact roots. Then, each tooth was coded and imaged three times using CBCT with and without metal artifact reduction algorithm and digital periapical radiography. Data were collected and statistically analyzed. Results: Digital periapical radiography showed statistically significantly lower diagnostic accuracy than CBCT modalities (P ≤ 0.05). The use of metal artifact reduction algorithm improved the diagnostic accuracy from CBCT1 to CBCT2 but with no statistically significant difference (P ≥ 0.05). Conclusion: From the study, we can conclude that in case of presence of metallic posts, CBCT with metal artifact reduction algorithm can improve detection of VRF.